Gestão educacional no contexto rural: implicações para o desempenho estudantil nos anos iniciais do ensino fundamental em uma escola ribeirinha no município de Breves (PA), de 2010 a 2014 - SILVA, Neide Andrade da (Universidade Federal do Pará, 2019)
This work arose from concern about the low quality of education in rural brevense. Presented as main intention to analyze the educational management and its implications for student achievement in the early years of primary education in rural areas of the municipality of Breves, in the period 2010-2014, with the empirical basis a riverside school. Delimited as the guiding question: what factors related to management, contributing to the poor performance of students in schools in rural communities in the municipality of Breves? To realize the intent of this research were carried out bibliographic research, documentary and field. With this study it was found that factors related to educational management as lack of school physical structure according to MEC standards, lack of educational teaching materials, lack of school food quality and especially lack of adequate school transport, among others, contribute significantly to the poor performance of students in schools in rural communities in the municipality of Breves